Diversity and community composition of herbaceous plants in different habitat types in south‐east Cameroon. (24th November 2017) - Willie, Jacob; Tagg, Nikki; Lens, Luc
Abstract: The composition of herbaceous vegetation was evaluated with the aim of characterizing forests at various ages of stand development. Herb stems were sampled in 250 4‐m² square plots distributed within six habitat types. A total of 36 herb species belonging to 15 families were recorded. Species richness did not significantly differ between habitat types. Most herb species occurred in all habitat types and were therefore generalists. However, a few indicator herb species were detected, and the results roughly suggested that herb species of the families Poaceae and Araceae were indicative of late successional forests; Zingiberaceae are indicative of early successional forests; and Commelinaceae, Costaceae, Cyperaceae and Marantaceae are indicators of flooded habitats. Species diversity and stem density of herbaceous plants did not change with forest succession as a decrease in abundance and frequency of occurrence of pioneer species in late successional forests was counterbalanced by the presence of generalist and late successional species. However, increasing proportions of dwarf stems in late successional forests translated to changes in the vertical structure of herbaceous plant communities. Herbivory pressure by gorillas did not have a notable effect on herbaceous plant community development. This study contributes to the definition of herbaceous ecological indicators of forest succession in different settings.